2012
DOI: 10.1007/978-3-642-33415-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Atlas Construction via Dictionary Learning and Group Sparsity

Abstract: Abstract. Atlas construction generally includes first an image registration step to normalize all images into a common space and then an atlas building step to fuse all the aligned images. Although numerous atlas construction studies have been performed to improve the accuracy of image registration step, simple averaging or weighted averaging is often used for the atlas building step. In this paper, we propose a novel patch-based sparse representation method for atlas construction, especially for the atlas bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Bias correction was then performed on all images with N3 method [Sled et al, 1998] to reduce the impact of intensity inhomogeneity and thus improve the performance of the subsequent image processing. Non-brain tissues such as skull and dura were stripped with a learning-based meta algorithm [Shi et al, 2012]. Finally, brain tissues were segmented into gray matter (GM), white matter (WM), and ventricular cerebrospinal fluid (CSF) using a coupled level-set algorithm [Wang et al, 2011].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bias correction was then performed on all images with N3 method [Sled et al, 1998] to reduce the impact of intensity inhomogeneity and thus improve the performance of the subsequent image processing. Non-brain tissues such as skull and dura were stripped with a learning-based meta algorithm [Shi et al, 2012]. Finally, brain tissues were segmented into gray matter (GM), white matter (WM), and ventricular cerebrospinal fluid (CSF) using a coupled level-set algorithm [Wang et al, 2011].…”
Section: Resultsmentioning
confidence: 99%
“…All image were preprocessed with the standard procedure which includes resampling, bias correction, skull stripping [Shi et al, 2012], and tissue segmentation [Wang et al, 2011]. The goal of image registration is to spatially normalize all preprocessed subject images into a common space, which is a necessary initial step for subsequent atlas building.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a sparse signal can be recovered from a small number of its linear measurements with high probability 2,8 . These sparsity priors are employed in many computer vision applications, such as, but not limited to, robust face recognition 38 , image restoration 26 , image bias estimation 56 , MR reconstruction 24,16 , atlas construction 34 , resolution enhancement 54 , image bias estimation 57,56 and automatic image annotation 47,13 . Sparsity methods have been proved to be very effective at handling gross errors or outliers.…”
Section: Relevant Workmentioning
confidence: 99%
“…Other methods 28,29 have focused on iteratively averaging the invertible elastic transformation of the template to better fit a target population. Additionally, template-free techniques 30,31 register all images simultaneously in a groupwise fashion; however, this is known to be computationally challenging due the size of the search space.…”
Section: Previous Workmentioning
confidence: 99%